2023
DOI: 10.1186/s41256-023-00328-9
|View full text |Cite
|
Sign up to set email alerts
|

Depression and health-related quality of life of patients with type 2 diabetes attending tertiary level hospitals in Dhaka, Bangladesh

Manish K. Namdeo,
Sarita Verma,
Rajat Das Gupta
et al.

Abstract: Introduction Type 2 diabetes mellitus (T2DM) and depression are closely linked. People with T2DM are at increased risk of developing depression and vice versa. T2DM and depression comorbid conditions adversely affect Health-Related Quality of Life (HRQOL) and management of T2DM. In this study, we assessed depression and HRQOL among patients with T2DM in Dhaka, Bangladesh. Methods A cross-sectional study was conducted in two tertiary-level hospitals… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 62 publications
(76 reference statements)
0
1
0
Order By: Relevance
“…The negative effects of depression on mental and behavioral states include a vast range of changes in feeling worthy, hopefulness, self-care behaviors, and quality of life [ 11 ]. Studies have indicated that depression is correlated with fundamental variables in the elderly, such as cognitive impairment [ 12 ], increased risk of hospital-treated conditions [ 13 ] increased suicide [ 14 ], and decreased health-related quality of life [ 15 , 16 ].…”
Section: Introductionmentioning
confidence: 99%
“…The negative effects of depression on mental and behavioral states include a vast range of changes in feeling worthy, hopefulness, self-care behaviors, and quality of life [ 11 ]. Studies have indicated that depression is correlated with fundamental variables in the elderly, such as cognitive impairment [ 12 ], increased risk of hospital-treated conditions [ 13 ] increased suicide [ 14 ], and decreased health-related quality of life [ 15 , 16 ].…”
Section: Introductionmentioning
confidence: 99%